Field Investigation on the Prevalence of Avian Influenza Virus Infection in Some Localities in Saudi Arabia - Abdullah N. Alkhalaf (Pakistan Veterinary Journal, 2010)
The objective of this study was to find out prevalence and types of avian influenza virus (AIV) among broilers, native chickens, ducks and pigeons in Saudi Arabia. Field investigation was carried out in four localities including Al-Qassim, Hail, Al-Jouf and Northern Border regions. Serum sample, tracheal and cloacal swabs were collected from broilers (n=1561), layers (n=988), ducks (n=329) and pigeons (n=450) from these localities and tested for three different avian influenza viruses (H9, H5 and H3) using Enzyme linked immunosorbent (ELISA) test, hamagglutination inhibition (HI test) and polymerase chain reaction (PCR). All tested samples were negative for H5 and H3 viruses. In contrast, all positive results were found to be for H9 AI virus using PCR, ELISA and HI test. Chicken sera tested by ELISA for AIV revealed the highest positive samples in Northern Border regions (45.71%), followed by Al-Jouf (29.65%), Al-Qassim (23.98%) and Hial (20.94%) with non-significant difference (χ2=5.983; P=0.112). HI test carried out on duck sera revealed 35.90% prevalence of antibodies against AIV. PCR amplification resulted in 34.28 and 21.36% positive samples in ducks and chickens, respectively. The highest (45.71%) PCR positive chicken samples were from Northern Border regions, followed by Al-Jouf (24.13%), Al-Qassim (19.30%) and Hail (16.69%) with significant difference (χ2=7.620; P=0.055). All tested pigeons samples were negative for the three virus serotypes included in the study.